Magnetic, thermal and spectral properties of Ni(II) 2,3- , 3,5- and 2,6-dimethoxybenzoates - Ferenc, Wieslawa; Walków-Dziewulska, Agnieszka; Sarzyński, Jan; Paszkowska, Barbara (Eclética Química, 2006)
Complexes of Ni(II) 2,3-, 3,5- and 2,6-dimethoxybenzoates have been synthesized, their physico-chemical properties have been compared and the influence of the position of –OCH3 sub- stituent on their properties investigated. The analysed compounds are crystalline, hydrated salts with green colour. The carboxylate ions show a bidentate chelating or bridging coordination modes. The thermal stabilities of Ni(II) dimethoxybenzoates were investigated in air in the range of 293-1173 K. The complexes decompose in three steps, yelding the NiO as the final product of decomposition. Their solubilities in water at 293 K are in the order of 10 -2 -10 -4 mol⋅dm -3 . The magnetic susceptibilities for the analysed dimethoxybenzoates of Ni(II) were measured over the range of 76-303 K and the mag- netic moments were calculated. The results reveal that the complexes are the high-spin ones and the ligands form the weak electrostatic field in the octahedral coordination sphere of the central Ni(II) ion. The various position –OCH3 groups in benzene ring cause the different steric, mesomeric and induc- tive effects on the electron density in benzene ring.